Invading brown bullhead catfish (Ameiurus nebulosus) show thermal niche rigidity and benthic niche plasticity: implications for management - Paul J. Blanchfield; Tazi H. Rodrigues; Calum MacNeil; Simon D. Stewart; Finnbar Lee; Brendan J. Hicks; Shane Grayling; Soweeta Fort-D’Ath; Matthew J. Prentice; Cindy Baker; Peter Williams; Robin J.P. Holmes (Biological Invasions, 2026)

Fish Futures in the Aftermath of the Invasion of Aotearoa New Zealand by the Freshwater Gold Clam ( Corbicula fluminea ) - Calum MacNeil (New Zealand Journal of Marine and Freshwater Research, 2026)
In 2023, the gold / Asian clam ( Corbicula fluminea ) was first recorded in Aotearoa New Zealand (Aotearoa‐NZ). This non‐native species (NNS) could impact Aotearoa‐NZ freshwater ecosystems more than any previous invader. It could alter food webs, physical habitats and water clarity, disrupt nutrient cycling and restructure plankton / macroinvertebrate / fish assemblages. I have reviewed clam impacts on trophic ecology, water chemistry and fish habitat from international studies, focusing on native and non‐native fish species also present in Aotearoa‐NZ and on ecological analogues. I identified fish that could be negatively affected and those which could benefit. Small benthic ‘riffle‐run specialists’ could be vulnerable to some extent, facing both habitat modification and competition for shared food resources. Fish frequenting backwaters or slower‐flowing reaches could be even more vulnerable, as clam densities are often highest here. Native galaxiids, already threatened by habitat fragmentation/degradation, may be at further risk from additional pressures of a clam invasion. Among introduced fish, salmonids may lose spawning habitats, whereas generalist ‘pests’ such as catfish and koi may benefit from clam‐derived food resources. C. fluminea may represent a significant new stressor for Aotearoa‐NZ freshwater ecosystems. The hyptheses generated in this article are important to help anticipate species‐specific responses, which will be essential for strategies to protect native fish.

Habitat suitability of Aotearoa New Zealand for the recently invaded gold clam ( Corbicula fluminea ) - Rose Somerville; Calum MacNeil; Finnbar Lee (New Zealand Journal of Marine and Freshwater Research, 2025)
The gold clam ( Corbicula fluminea) is a highly invasive freshwater mollusc, which was detected in Aotearoa New Zealand in 2023. Currently, C. fluminea has only been observed in the Waikato catchment, but there is significant concern it will spread across the country. There is an urgent need to identify suitable habitat for the species beyond the Waikato, given the high probability of spread. Here, we used a Maximum Entropy (MaxEnt) model to predict habitat suitability across Aotearoa for C. fluminea . The model was parametrised with 9,544 observations from across the species’ native and invaded ranges and seven climate, environmental and habitat variables associated with the species’ distribution. The highest risk area are mostly located in Te Ika‐a‐Māui (North Island), in particular, northern Waikato, Auckland, Northland, Bay of Plenty, Hawke's Bay and in Te Waipounamu (South Island) areas with the highest habitat suitability included Marlborough, North Canterbury and Christchurch. Our findings suggest there are many invadable areas beyond the Waikato and a strategy of containment and suppression of existing C. fluminea populations should now be a priority, given the difficulty of eradication once further spread has occurred and new populations are well established.

Differences in the abilities of native and invasive amphipods to tolerate poor water quality and recolonise degraded habitats - Calum MacNeil (Hydrobiologia, 2019)

Predatory impacts of the invasive ‘killer shrimp’ Dikerogammarus villosus on a resident amphipod and isopod (Crustacea: Malacostraca) are influenced by water quality and habitat type - Calum MacNeil (Hydrobiologia, 2019)

Natural born killers: an invasive amphipod is predatory throughout its life-history - Jaimie T. A. Dick; Mhairi E. Alexander; Calum MacNeil (Biological Invasions, 2013)

Differential predatory and interference interactions between native and invasive freshwater amphipods and a co-occurring mysid (Crustacea) - Calum MacNeil; Jaimie T. A. Dick (Hydrobiologia, 2012)

Parasite-mediated intraguild predation as one of the drivers of co-existence and exclusion among invasive and native amphipods (Crustacea) - Calum MacNeil; Jaimie T. A. Dick (Hydrobiologia, 2011)

An appraisal of a biocontamination assessment method for freshwater macroinvertebrate assemblages; a practical way to measure a significant biological pressure? - Calum MacNeil; Mark Briffa; Rob S. E. W. Leuven; Fiona R. Gell; Richard Selman (Hydrobiologia, 2010)

Replacement of a native freshwater macroinvertebrate species by an invader: implications for biological water quality monitoring - Calum MacNeil; Mark Briffa (Hydrobiologia, 2009)

Invader–invader interactions in relation to environmental heterogeneity leads to zonation of two invasive amphipods, Dikerogammarus villosus (Sowinsky) and Gammarus tigrinus Sexton: amphipod pilot species project (AMPIS) report 6 - Dirk Platvoet; Jaimie T. A. Dick; Calum MacNeil; Mariëlle C. van Riel; Gerard van der Velde (Biological Invasions, 2009)

Environmental mediation of intraguild predation between the freshwater invader Gammarus pulex and the native G. duebeni celticus - Christophe Piscart; Jaimie T. A. Dick; David McCrisken; Calum MacNeil (Biological Invasions, 2009)

A species invasion mediated through habitat structure, intraguild predation, and parasitism - Calum MacNeil; Jaimie T. A. Dick; Mark P. Johnson; Melanie J. Hatcher; Alison M. Dunn (Limnology and Oceanography, 2004)
With field, laboratory, and modeling approaches, we examined the interplay among habitat structure, intraguild predation (IGP), and parasitism in an ongoing species invasion. Native Gammarus duebeni celticus (Crustacea: Amphipoda) are often, but not always, replaced by the invader Gammarus pulex through differential IGP. The muscle‐wasting microsporidian parasite Pleistophora mulleri infects the native but not the invader. We found a highly variable prevalence of P. mulleri in uninvaded rivers, with 0–91% of hosts parasitized per sample. In addition, unparasitized natives dominated fast‐flowing riffle patches of river, whereas parasitized individuals dominated slower‐flowing, pooled patches. We examined the survivorship of invader and native in single and mixed‐species microcosms with high, intermediate, and zero parasite prevalence. G. pulex survivorship was high in all treatments, whereas G. duebeni subsp. celticus survivorship was significantly lower in the presence of the invader. Further, parasitized G. duebeni subsp. celticus experienced near‐total elimination. Models of the species replacement process implied that parasite‐enhanced IGP would make invasion by G. pulex more likely, regardless of habitat and parasite spatial structure. However, where heterogeneity in parasite prevalence creates a landscape of patches with different susceptibilities to invasion, G. pulex may succeed in cases where invasion would not be possible if patches were equivalent. The different responses of parasitized and unparasitized G. duebeni subsp. celticus to environmental heterogeneity potentially link landscape patterns to the success or failure of the invasion process.